DETEKSI DINI TEKANAN DARAH, GULA DARAH, ASAM URAT, DAN KOLESTEROL WARGA - Iswantiningsih, Elisabeth; Istiqomah, Istiqomah; Hapsari, Agustina Retno; Mualifah, Laily; Sulistyowati, Endang Tri (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2025)
Routine health checks are essential strategies for the early detection of non-communicable diseases (NCDs) in communities. This study was conducted in Dusun Mangir Tengah, Sendangsari, Pajangan, Bantul Regency, involving 68 residents aged <20 years (15), 21–40 years (25), and >40 years (28). The examination included blood pressure, blood glucose, uric acid, and cholesterol, accompanied by brief education on healthy lifestyle management. Results indicate that blood pressure increases with age, with residents >40 years classified as hypertensive or prehypertensive. Most participants had normal blood glucose and uric acid levels, though some adults and elderly approached high thresholds. Cholesterol levels were elevated in older adults, indicating potential risks of heart disease and hypertension. These findings emphasize the importance of community-based health screening as a tool for early detection, education, and preventive intervention. Regular educational programs, periodic screenings, and health promotion activities are recommended to enhance community awareness and enable effective NCD risk management